Malaria, sexual development and transmission: retrospect and prospect. - Sinden, R (2009)
It is difficult to recapture the excitement of recent research into the malaria parasites. Plasmodium has shown itself to be a most elegant, resourceful and downright devious cell. To reveal any of its manifold secrets is a hard-won privilege. The thrill of this intellectual endeavour, however, has to be tempered by the realism that we have made unremarkable progress in attacking malaria in the field, where it remains almost as omnipresent as it ever was in the 19th and 20th centuries, and both the parasite and vector have become more difficult to control than ever before. This personal view looks back at the significant progress made, and forward to the challenges of the future, focusing on work on sexual development.